A mass transfer model for hydrate formation in bubbly flow considering bubble-bubble interactions and bubble-hydrate particle interactions. (December 2018) - Fu, Weiqi; Wang, Zhiyuan; Sun, Baojiang; Chen, Litao
Highlights: The hydrate formation in swarms does not simply equal to the weighted sum of hydrate formation on single moving bubble. Both the bubble-bubble interaction and the bubble-hydrate particle interaction will increase mass transfer phenomenon in bubbly flow and increase hydrate formation rate. A mass transfer model is developed considering effects of the bubble-bubble interaction and the bubble-hydrate particle interaction. Abstract: Methane hydrate formation in bubbly flow widely exists in development of oil, gas and natural gas hydrate in deep-water environment, as an important flow assurance problem. The hydrate formation in swarms is a mass transfer process and does not simply equal to the weighted sum of hydrate formation on single moving bubble. The bubble-bubble interactions and the bubble-hydrate particle interactions in bubbly flow will promote the mass transfer coefficient during hydrate formation and accelerate hydrate formation in bubbly flow. Meanwhile, series of experiments are performed to investigate characteristics of hydrate formation in bubbly flow under Re from 15, 000 to 22, 000. The hydrate formation rate and the mass transfer coefficient increase with the fluid velocity increases. The mass transfer coefficient ascends exponentially with time because the increase of quantities of hydrate particles in flow loop create more interactions between bubbles and hydrate particles. The increase of mass transfer coefficient further compensates the reduction of hydrate formation rate induced by subcooling temperature decreasing in experiments. A mass transfer hydrate formation model is developed to depict hydrate formation in bubbly flow including the bubble-bubble interaction factor and the bubble-hydrate particle interaction factor and reaches a good agreement with experimental data.